Tradisi Penyelesaian Sengketa Kewarisan Masyarakat Kalimantan Tengah (Studi pada Kabupaten Katingan dan Kota Palangka Raya) - Pelu, Ibnu Elmi Achmat Slamat; Syaikhu, Ahmad; Tarantang, Jefry (Fakultas Syariah IAIN Purwokerto, 2019)
The people of Central Kalimantan, especially in the District of Katingan and the City of Palangka Raya in resolving inheritance disputes prioritize deliberations by peaceful means and do not conflict with Islamic law. Because, Islamic law also accommodates customary laws, as long as it does not conflict with Islamic tenets. The tradition of resolving the inheritance disputes of the people of Central Kalimantan in the Katingan Regency and Palangka Raya City is in accordance with the custom in resolving inheritance disputes prioritizing peace by using Islamic law first and then holding a meeting to agree on the determination of shares and distribution of assets. The legal enforcement of the settlement of inheritance disputes in the community is recognized absolutely and they also apply farÄâ€™id (Islamic inheritance) law first, then deliberations are carried out in a family consensus with the principle of peace.